Spatial variations in the microbiota: comparative analysis of microbial composition and predicted functions across different intestinal segments and feces in donkeys - Wang, Yanwei; Hu, Tong; Liang, Kaixuan; Li, Shinuo; Zhang, Qiyue; Li, Wenqiang; Qu, Honglei; Dong, Boying; Zhang, Haihua; Ma, Qiugang; Jia, Ru; Huang, Shimeng (Frontiers in Microbiology, 2025)
Donkeys, as single-stomach herbivores, have a complex and diverse microbial community in their digestive tracts. The intestinal bacterial community is crucial for maintaining intestinal homeostasis, as well as the host’s overall nutrition and health. However, research on donkey gut microbes is relatively limited, particularly regarding the microbial colonization patterns in different intestinal segments of adult donkeys. Therefore, this study examined the abundance and function of microbiota across various sites of the intestinal tract (duodenum, jejunum, ileum, cecum, colon) and feces of healthy adult Dezhou male donkeys using 16S rRNA gene sequencing and PICRUSt analysis. The results indicate that donkeys have a rich gut microbial diversity and a large microbial population. No significant differences in the indices of alpha diversity were observed among the donkey’s duodenum, jejunum, ileum, cecum, colon, and feces. A Venn diagram analysis revealed the presence of both unique (Duodenum: 4645; Jejunum: 3586; Ileum: 4904; Cecum: 4253; Colon: 6135; Feces: 4885) and shared (339) ASVs among the different sections. A principal coordinate analysis (PCoA) revealed significant differences (R2 = 0.2076, p < 0.007) across the six intestinal segments of the donkeys. At the phylum level, Firmicutes (63.64%), Bacteroidetes (20.72%), Verrucomicrobiota (9.16%), Patescibacteria (1.95%), Spirochaetota (1.87%), Actinobacteriota (1.13%), and Proteobacteria (0.42%) were the dominant bacteria in all samples. The Wilcoxon rank-sum test revealed significant differences in the proportions of genera among different intestinal segments. Specific genera were significantly enriched in various segments: Lachnospiraceae_UCG-008 and Sphaerochaeta in the duodenum; Christensenellaceae_R-7_group and Bacillus in the jejunum; NK4A214_group and Alloprevotella in the ileum; UCG-005 and Lactobacillus in the cecum; Clostridium_sensu_stricto_1 and Chlamydia in the colon; and Rikenellaceae_RC9_gut_group and Prevotellaceae_UCG-004 in the feces. A PICRUSt2 functional prediction analysis indicated that carbohydrate metabolism, prokaryotic cellular communities, antimicrobial drug resistance, immune diseases, membrane transport, signal transduction, and transcription exhibited significant differences among the different intestinal segments. This study provided critical primary data on the differences in donkey gut microbiota and the synergistic effects between gut microbiota and host functions. These findings can be used to assess donkey health status, improve breeding, and develop microbial additives.